2014
DOI: 10.1088/0029-5515/54/8/083007
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional distortions of the tokamak plasma boundary: boundary displacements in the presence of saturated MHD instabilities

Abstract: The three-dimensional plasma boundary displacement induced by long-lasting core magnetohydrodynamic (MHD) instabilities has been measured in JET, MAST and NSTX. Only saturated instabilities are considered here since transient rapidly growing modes which degrade confinement and act as potential triggers for disruptions bring more fundamental concerns than boundary displacements. The measured displacements are usually small, although in extreme cases in MAST when the rotation braking is strong, a significant glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…The magnitude of the distortion strongly depends on the minimum value of the safety factor q min . 3,9,10,13 In evaluating the dependence, here, q min is varied by changing a in q ¼ ð0:7 þ ð0:7 þ aÞs Àð1 þ aÞs 4 Þ À1 with keeping qðq ¼ 0Þ and qðq ¼ 1Þ as is done in Ref. 9.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitude of the distortion strongly depends on the minimum value of the safety factor q min . 3,9,10,13 In evaluating the dependence, here, q min is varied by changing a in q ¼ ð0:7 þ ð0:7 þ aÞs Àð1 þ aÞs 4 Þ À1 with keeping qðq ¼ 0Þ and qðq ¼ 1Þ as is done in Ref. 9.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…For instance, the ITER hybrid scenario has a q-profile that is nearly flat and close to unity in the core region, 1 leading to, for example, a better dependence of turbulent transport on b because of weak magnetic shear in the core. 2 A helical distortion of the magnetic axis is observed for such a q-profile in some tokamaks, JET, MAST, and NCSX testing the hybrid scenario, 3 that is called as the snake, 4 the helical core, and the longlived mode. Analysis on helical cores was extended to DIII-D, Alcator C-Mod, and JT-60U.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distortion of the OMP is expected to be less than ± 1.75% of the minor radius for 15 MA H-mode plasmas, i.e. about ± 3.5 cm around the nominal OMP position [6,7]. This perturbation (n = 3 toroidal mode in ITER) will not be static and it will rotate toroidally with the frequency of a few Hz.…”
Section: Field Line Tracing Simulationsmentioning
confidence: 98%
“…These 3D boundary displacements have been studied in multiple machines and reviewed in Ref. [15], which concludes that the magnitude of the edge displacement scales linearly with the applied MPs calculated by vacuum field modeling. However, in some cases, it was observed that vacuum modeling drastically underestimated the 3D displacement due to the stable kink response [16] [17].…”
Section: Introductionmentioning
confidence: 99%